Atlas of EEG, seizure semiology, and management - Misulis, Karl E; Sonmezturk, Hasan H; Ess, Kevin C; Abou-Khalil, Bassel (Oxford University Press, 2022)
"Electroencephalography (EEG) is an invaluable tool for evaluating patients with suspected seizures or encephalopathy, yet EEG is only one source of data, so information from this technology must be integrated with knowledge of basic science and clinical neurology. This work has a principal focus on EEG, but interleaves that discussion with information on seizures, epilepsy, encephalopathy, and other neurologic conditions for which EEG can be a useful diagnostic tool"--
Keywords: elektroencefalografie; Electroencephalography; záchvaty; Seizures; neurologie